2019
DOI: 10.1111/ajt.15072
|View full text |Cite
|
Sign up to set email alerts
|

C5aR1 regulates migration of suppressive myeloid cells required for costimulatory blockade-induced murine allograft survival

Abstract: Costimulatory blockade-induced murine cardiac allograft survival requires intragraft accumulation of CD11b Ly6C Ly6G regulatory myeloid cells (Mregs) that expand regulatory T cells (Tregs) and suppress effector T cells (Teffs). We previously showed that C5a receptor (C5aR1) signaling on T cells activates Teffs and inhibits Tregs, but whether and/or how C5aR1 affects Mregs required for transplant survival is unknown. Although BALB/c hearts survived >60 days in anti-CD154 (MR1)-treated or cytotoxic T-lymphocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…These assays showed ~10-fold fewer splenic IFNγ + , TNFα + and CD107 + CD8 + T cells vs. the untreated recipients on day 6 (regardless of C3aR1 expression, compare to Figure 1) and demonstrated that spleens obtained from the tacrolimus-treated C3ar1 −/− recipients contained significantly fewer donor-reactive IFNγ + (Figure 2B top, 2C), TNFα + (Figure 2B bottom, 2D), and CD107a/b + (Figure 2E) CD8 + T cells than tacrolimustreated WT controls. While we observed no differences in T REG numbers between groups, ( Figure 2F), calculated donor-reactive, IFNγ-or TNFα-producing T EFF :T REG ratios ( Figure 2G-H) were lower in the C3ar1 −/− recipients, indicative of enhanced T REG function (34). We similarly observed 2-fold lower numbers of IFNγ + , TNFα + and CD107 + splenic CD8 + T cells in the day 10 post-transplant tacrolimus+C3aR1-A treated recipients vs. tacrolimus treated controls (p<0.05 for each, n=4/group, data not shown).…”
Section: Blockade Of C3ar1 Signaling Synergizes With Tacrolimus To Prmentioning
confidence: 61%
“…These assays showed ~10-fold fewer splenic IFNγ + , TNFα + and CD107 + CD8 + T cells vs. the untreated recipients on day 6 (regardless of C3aR1 expression, compare to Figure 1) and demonstrated that spleens obtained from the tacrolimus-treated C3ar1 −/− recipients contained significantly fewer donor-reactive IFNγ + (Figure 2B top, 2C), TNFα + (Figure 2B bottom, 2D), and CD107a/b + (Figure 2E) CD8 + T cells than tacrolimustreated WT controls. While we observed no differences in T REG numbers between groups, ( Figure 2F), calculated donor-reactive, IFNγ-or TNFα-producing T EFF :T REG ratios ( Figure 2G-H) were lower in the C3ar1 −/− recipients, indicative of enhanced T REG function (34). We similarly observed 2-fold lower numbers of IFNγ + , TNFα + and CD107 + splenic CD8 + T cells in the day 10 post-transplant tacrolimus+C3aR1-A treated recipients vs. tacrolimus treated controls (p<0.05 for each, n=4/group, data not shown).…”
Section: Blockade Of C3ar1 Signaling Synergizes With Tacrolimus To Prmentioning
confidence: 61%
“…Using novel myeloid-cell specific C5aR1 conditional knockout mice, Llaudo et al showed C5a/C5aR1 signaling on myeloid cells is a key mediator of regulatory myeloid cell induction/function post-transplant. Absence of C5aR1 specifically on myeloid cells (and not granulocytes) increased anti-donor T cell immunity, decreased T REG , and accelerated graft rejection despite costimulatory blockade (43).…”
Section: Complement and T Cell-mediated Rejectionmentioning
confidence: 96%
“…44 The development of drugs blocking the complement, such as eculizumab that targets C5, could not only improve the management of aHUS 45 but also kidney transplantrelated complications. 44,46 Multiple fields have been renovated by growing knowledge of diverse mutation of clinical interest. Corinne Antignac's (Inserm U1163, Paris, France) presentation focused specifically on hereditary forms of focal segmental glomerulosclerosis (FSGS), a podocytopathy associated with proteinuria.…”
Section: Hopes and Shortcomings Of "Nephrogenomics" And "Transplantommentioning
confidence: 99%